Research on "Four Realities" Teaching Concept and "TOPIC" Teaching Mode Based on Undergraduate Marketing Course - Man Guo; Qian Zhao (International Journal of Management and Education in Human Development, 2023)
In the teaching of marketing courses, this research focuses on the lack of students' awareness of exploring and previewing before class; the effect of group activities in class is insufficient; the ability to expand practice after the class is lacking; the feedback of teaching effect is slow to obtain, and teaching strategies are adjusted slowly, these four "pain points" in teaching, based on the analysis of teaching practice and the learning situation, I specially designed and constructed the "four realities" teaching concept, created the "TOPIC" teaching model, and created the "multiple and all-round evaluation system" as a highlight of teaching innovation design, the elements of ideological and political education are based on "cultivating people with morality, taking responsibility for the times, social responsibility, family and country feelings, practicing socialist core values, establishing and strengthening cultural self-confidence, and enhancing national pride. Use the “Xuexitong” APP to carry out teaching content, teaching process design, and whole process information management. The formulation and implementation of the "Four Realities" teaching concept and the "TOPIC" teaching model, it has effectively achieved the teacher's direction and individual lessons. Exploration in the front; the teaching process is designed, and the group class is good at discussion; the advanced development is in-depth, innovation and challenges are strong in practice; the teaching effect is responsive, and the teaching strategy is adjusted immediately